GE_GERICHTE A/2518/2022 vom 11. August 2022 - GE Cour de justice (2022)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION | LEI.69.al2; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4; LEI.76.al1.letb.ch1; LEI.75.al1.letc; LEI.79; LEI.80.al6; LEI.83.al4